Effects of Ta Content on the Electrical Properties of Lead-Free (K0.44Na0.52Li0.04)(Nb0.96-xTaxSb0.04)O3 Ceramics. Issue 1 (2nd January 2016) - Zhang, Zhiqiang; Yang, Jie; Liu, Zhifu; Li, Yongxiang
Abstract : Lead-free piezoelectric ceramics with the composition of (K0.44 Na0.52 Li0.04 )(Nb0.96-x Tax Sb0.04 )O3 (KNLNTx S) were prepared by the conventional solid-state reaction method. The effects of Ta content on the phase structure, microstructure and electrical properties of KNLNTx S ceramics were investigated. The effect of poling temperature on piezoelectric properties of KNLNTx S ceramics was also studied in detail. Enhanced piezoelectric properties ( d 33 = 315 pC/N, k p = 0.49 and k t = 0.48) with low dielectric loss (tanδ < 0.06) were obtained in the ceramics with x = 0.10 under optimum poling temperature (140°C), indicating that KNLNTx S ceramic is a promising lead-free piezoelectric candidate material.